Making a Difference Across Kansas, K-State Research and Extension Programming Report 2023-24 - Hadley, Gregg (My University, 2025)
K-State Research and Extension's program report for 2023-2024. This report to a variety of stakeholders illustrates the statewide extension work for the programming year.
RPT118_2025_01
Keywords: RPT118; Administrative and Research Reports